The Template‐Free Synthesis of CuO@CeO2 Nanospheres: Facile Strategy, Structure Optimization, and Enhanced Catalytic Activity toward CO Oxidation. Issue 25 (25th June 2018) - Su, Yunfei; Yuan, Shanshan; Ning, Dandan; Zhang, Qingwen; Han, Weiliang; Wang, Yi
Abstract : The template‐free construction of hollow multiporous materials with hierarchically multiporous walls, unique morphologies, and functionalities remains a great challenge in materials science. Here, we describe a facile template‐free approach to synthesize hollow multiporous‐walled CeO2 (HMW‐CeO2 ) nanospheres. The HMW‐CeO2 nanosphere possesses a hierarchically multiporous wall, with pore sizes ranging from micropores to mesopores, centered at 0.43, 4.2, and 14.3 nm. The CuO loaded HMW‐CeO2 support (HMW‐CuO@CeO2 ) is evaluated for its catalytic activity in a CO oxidation reaction. The HMW‐CuO@CeO2 support exhibits a higher catalytic activity than all of the other CeO2 catalysts. The results show a low T 100 of about 60 °C (the temperature at which 100 % CO conversion has been achieved) and high stability, with negligible decrease in the CO conversion during 12 h of reaction. Overall, it provides a simple, low‐cost and mass‐productive method for the preparation of highly active catalysts for CO oxidation. Abstract : Here, we describe a facile template‐free approach to synthesize hollow hierarchically multiporous‐walled CeO2 (HMW‐CeO2 ) nanospheres. The CuO loaded HMW‐CeO2 support (HMW‐CuO@CeO2 ) is evaluated for its catalytic activity in a CO oxidation reaction. The catalytic activity of HMW‐CuO@CeO2 remains unchanged after three cycles and no loss of CO conversion is observed for up to 12 h on stream at 60 °C.